OʻZBEKISTONDA TA’LIM SOHASIDAGI XALQARO HAMKORLIK: HOLATI, YOʻNALISHLARI VA ISTIQBOLLARI (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article scientifically analyzes the policy of international cooperation in the field of education in the Republic of Uzbekistan, its legal framework, main directions and practical results. Mechanisms of cooperation with international organizations, foreign countries and leading higher education institutions, joint educational programs, academic exchanges and projects aimed at improving the quality of education are highlighted. The role of international cooperation in the modernization of the education system and its future development prospects are also substantiated.